Uganda Country Economic Memorandum : Economic Diversification and Growth in the Era of Oil and Volatility - World Bank; Government of Uganda (World Bank, Kampala, Uganda, 2016)
The objective of the Ugandan government is to make Uganda an upper - middle income country within thirty years. Economic diversification is a key component of that strategy. The country economic memorandum (CEM) report discusses how the emergence of oil and mineral production can contribute to Uganda’s effort to promote economic diversification as a means to achieve sustainable and shared growth. Based on the lessons from international experience, the report outlines the elements of a development and diversification strategy, which the Ugandan government may wish to consider in the design of its macroeconomic, fiscal, and sectoral development policies. It then focuses on the set of policies required to maximize the benefits of a diversification strategy in an oil-producing country. Finally it describes a series of actions which the government should plan, and carry out to deal with a number of specific implementation issues. The first part of the report focuses on the importance of economic diversification for Uganda and on the prospects and challenges of oil and mineral development. It addresses the following three issues: (a) why diversification is important for economic development?; (b) where Uganda stands in that area and why it should give a new impetus to its diversification strategy?; and (c) what are the prospects, possible impact, and challenges associated to oil and mining development for Uganda’s economy?